Analisis Visual Penerapan 12 Prinsip Animasi pada Film Animasi “Battle of Surabaya” - Maelani, Yusi (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
Animation is a moving image formed from a series of arranged images. In creating animation, there are 12 principles to make the animation look more realistic and interesting. These 12 principles of animation were developed by Disney animators Frank Thomas and Ollie Johnston in 1981. In this study, we will observe how the 12 principles of animation are applied in the animated film “Battle of Surabaya” to determine how effective these principles are in making animation more realistic. The purpose of this study is to explain the application of the 12 principles of animation in scenes from the animated film “Battle of Surabaya.” The qualitative descriptive method was used in this study, employing visual observation, literature study, and documentation as data collection techniques. The results of this study show that the application of the 12 principles of animation in the animated film “Battle of Surabaya” has been proven to improve the quality of the animation and make the film feel more realistic, thereby achieving more interesting results.